124
приводим к общему знасенателю
lim(n->∞) ((n^2+2n-1)/3n - n/3) = lim (n->∞)( n^2 + 2n - 1 - n^2)/3n = lim (n->∞) (2n-1)/3n ={делим на n числитель и знаменатель} = lim (n->∞) (2 - 1/n)/3 = (2 - 0)/3 = 2/3
214
lim (x->0) (2 - √(4+x))/2x = домножаем на 2 + √(4+x) = lim (x->0) (2 - √(4+x))*(2 + √(4+x)))/2x(2 + √(4+x)) = lim(x->0) ( 4 - 4 - x)/2x(2 + √(4+x)) = lim(x->0) - x/2x(2 + √(4+x)) = - 1/2(2+√(4+0)) = 1/2(2+2) = 1/8
Автор:
boomerДобавить свой ответ
Предмет:
Немецкий языкАвтор:
buddiefoxОтветов:
Смотреть
Предмет:
БиологияАвтор:
vanesamirandaОтветов:
Смотреть